Childhood vulnerability to drowning in the Western Cape, South Africa: Risk differences across age and sex. (5th June 2020) - Simons, Abigail; Govender, Rajen; Saunders, Colleen Jayne; Singh‐Adriaanse, Robyn; Van Niekerk, Ashley
Abstract: Introduction: Drowning is amongst the leading causes of death of children and young people worldwide, with high concentrations in Southeast Asia and Sub‐Saharan Africa. In the Western Cape province in South Africa, drowning mortality rates for children were reported at 3.8 per 100, 000 population. Internationally, evidence suggests that unimpeded access to water bodies and containers and lapses in supervision together with the child's limited developmental capacities, place children at greater risk of drowning. This study examined the risk for fatal drowning by age cohort and sex in child and adolescent (0–19 years old) in the Western Cape. Method: Demographic and descriptive data for child drowning fatalities from 2010 to 2016 were obtained from the Western Cape Forensic Pathology Service. Descriptive variables included location of drowning incident by body of water, time of day, day of week and season. Data were analysed by age cohorts aligned to child psychosocial developmental stages. Descriptive statistics reported fatality frequencies by age cohort and sex, and logistic regression was conducted to detect differences in drowning risk across these categories. Results: A total of 538 childhood drowning fatalities were analysed, with the highest proportion occurring in children aged 13–19 years (29.6%) and the majority occurring in males (75.8%). Sex, location of drowning incident and season were significant predictors of drowning across the age cohorts. Relative to females, males between ages 0–1 and 2–3 years were less likely to drown when compared with older children. Conclusion: This study confirms existing evidence that children younger than five are most at risk of drowning. In contrast to international and local research findings that have indicated a similar or higher risk for drowning amongst boys compared with girls aged 3 years and younger, this study identified that males were less likely to drown between the ages of 0 and 3 years compared with girls.